Pengaruh Massa Surfaktan P104 terhadap Kristalinitas dan Ukuran Kristal Silika Mesopori - Ahdiatun Nuri; Syamsi Aini (Jurnal Periodic Jurusan Kimia UNP, 2021)
Mesoporous silica is a silka solid that has a pore size between 2-50 nm and can be used in various fields such as a catalyst, drug diluents, sensors, adsorption, stationary phase for chromatography and others. Mesoporous silica was synthesized using the precursor natrum silicate (Na2SiO3) from silica sand because it is more economical and easy to obtain. This study aims to determine the effect of Pluronic 104 (1g; 1.5g; and 2g) surfactant on particle size and crystallinity of mesoporous silica with Na2SiO3 as a base material synthesized from silica sand. Mesoporous silica was synthesized using the sol-gel method because it can be done at low temperature, then followed by calcination at 550 °C for 5 hours to remove the template. The synthesized Mesoporous silica was characterized using high angle X-Ray Diffraction (XRD) 2θ = 10°-80°. The results of XRD data measurements showed a diffraction pattern that appeared as wide and low peaks at 2θ = 22°; 21.9°; 22.7° for products SM01, SM02 and SM03 respectively indicate that the synthesized silica is amorphous. Mesoporous silica with the highest  intensity and crystallinity was obtained in the SM03 sample with the addition of 2 grams of P104.